LOOKING BACK : THE MASTER OF LIBRARY AND INFORMATION SCIENCE PROGRAMME AT THE UNIVERSITY OF MALAYA, MALAYSIA - N.N., Edzan; Abrizah, Abdullah (Malaysian Journal of Library and Information Science, 2003)
Traces the development of library science education programmes in Malaysia, which started out as early as 1955. Describes the MLIS programme conducted at the University of Malaya and the account of thinking that went into the revised MLIS curriculum. Outlines the various steps taken to review the programme’s curriculum in keeping with new demands from prospective employers. The programme has been running since 1996. Briefly touches on the LIS research that has helped to enrich the pool of local LIS publications